المنهج التاريخي عند محمد ناصر في كتابه الشعر الجزائري الحديث اتجاهاته وخصائصه الفنية - عزيز, حليمة; هيمة, عبد الحميد (جامعة الوادي - University of Eloued, 2021)
في هذا المقال نستعرض جانبا من الخطاب النقدي للدكتور محمد ناصر من خلال كتابه "الشعر الجزائري الحديث –اتجاهاته وخصائصه الفنية (1925-1975)"،الذي أولى فيه أهمية للمناهج السياقية، التي هيمنت على الساحة النقدية في الجزائر منذ بداية الستينيات، وأخص بالذكر المنهج التاريخي الذي اعتده محمد ناصر لقراءة المدونة الشعرية، من خلال التركيز على المعطيات التاريخية المتعلقة بحياة الشعراء الجزائريين وعصرهم، ظروف حياتهم وبيئتهم التي أثرت في إبداعاتهم، واتجاهاتهم الأدبية، وسنحاول هذا البحث التعرف على طبيعة المنهج النقدي عند محمد صالح ناصر، ومدى تمثله الرؤية التاريخية التي اعتنى فيها بدراسة العوامل البيئية التي وجهت الشاعر الجزائري إلى الاتجاه الوجداني في الشعر . This article reviews a brief part of the critical discourse that was discussed by the critic Dr. MOHEMMED NACER (1938) in his book Modern Algerian Poetry: Its Trends and Artistic Characteristics (1925-1975), where he stressed the significance of the contextual approaches that dominated the monetary arena in Algeria since the beginning of the 1960's. This study, In particular, highlights the historical method of Dr. NACER's research of the Historical data. The latter mentioned is related to both the life and the age of Algerian Poets, in addition to their life conditions and their environment which affect their creativity and their literary trends. Significantly, this article aims to identify the nature of the Critical approach in the view of Dr. MOHEMMED NACER in which he represents the historical vision. He, further, gave a huge importance to the study of external contexts. In this context, the Emotional Romantic Algerian Poets faced to adopt the Romantic trend in his book Modern Algerian Poetry (Study of the Media of Romantic Poets in Algeria).
مقال
Keywords: Dr. MOHEMMED NACER; Emotional Romantic Algerian Poets; Historical approach; Modern Algerian Poetry; pioneering of romantic poetry; study